An update on evolutionary, structural, and functional studies of receptor-like kinases in plants - Liu, Jing; Li, Wenjuan; Wu, Guang; Ali, Khawar (Frontiers in Plant Science, 2024)
All living organisms must develop mechanisms to cope with and adapt to the new environments. The transition of plants from aquatic to terrestrial environment provided new opportunities for them to exploit additional resources but made them vulnerable to harsh and ever-changing conditions. As such, the transmembrane receptor-like kinases (RLKs) have been extensively duplicated and expanded in land plants, peaking the number of RLKs in the advanced angiosperms, thus becoming one of the largest protein families in eukaryotes. The basic structure of the RLKs consists of a variable extracellular domain (ECD), a transmembrane domain (TM), and a conserved kinase domain (KD).While their variable ECDs can perceive various kinds of ligands that activate the conserved KD through a series of auto-and trans-phosphorylation events, allowing the KDs to keep the conserved kinase activities as a molecular switch that stabilizes their intracellular signaling cascades, possibly maintaining cellular homeostasis as their advantages in different environmental conditions. The RLKs signaling mechanisms may require a coreceptor and other interactors, which ultimately leads to the control of various functions of growth and development, fertilization, and immunity. Therefore, the identification of new signaling mechanisms might offer a unique insight into the regulatory mechanism of RLKs in plant development and adaptations. Here we give an overview update of recent advances in RLKs and their signaling mechanisms.